Histopathology of Placenta Creta: Chorionic Villi Intrusion into Myometrial Vascular Spaces and Extravillous Trophoblast Proliferation are Frequent and Specific Findings With Implications for Diagnosis and Pathogenesis. (November 2016) - Parra-Herran, Carlos; Djordjevic, Bojana
Abstract : Placenta creta is characterized by invasion of placental villi into the myometrium in the setting of a dysfunctional or absent decidua. Histopathologic diagnosis of placenta creta is important, particularly in cases of hysterectomy because of unanticipated intractable postpartum hemorrhage. Previous studies have documented a higher amount and depth of myometrial infiltration by the implantation site intermediate trophoblast compared with controls. In addition, we have anecdotally observed chorionic villi in myometrial vascular spaces in specimens with placenta creta. The aim of this study was to explore the prevalence and specificity of these features. Sixty-one postpartum hysterectomies, 44 with placenta creta and 17 without were reviewed. Villous intrusion into vascular spaces was recorded. Using immunohistochemistry for GATA3, the amount of intermediate trophoblast (number of positive cells in five 40× fields) and depth of trophoblast myometrial infiltration were assessed. Mean gestational ages of the creta group (34.4 yr; range, 20–43 yr) and control group (35 yr; range, 25–51 yr) were comparable. Presence of chorionic villi in myometrial vascular spaces was frequent in placenta creta: 31/44 versus 1/17 controls (70.4% vs. 5.8%, P <0.0001). This finding was more common in the percreta (87.5%) and increta (84%) than in the accreta (27.2%, P =0.0008). Mean depth of trophoblast myometrial invasion was greater in cretas (47.9%) than in controls (14.5%, P =0.004). Likewise, mean distance of deepest trophoblast to serosa was shorter in the cretas (7.3 mm) than in controls (23.8 mm, P <0.0001). These differences were, however, attributable to placentas increta and percreta. When only accretas and controls were compared, the myometrial depth of trophoblast was similar. The mean intermediate trophoblast cell count in the placental bed was greater in cretas (664) than in controls (288, P <0.0001). Such difference was seen in all creta cases despite the type (accreta 639, increta 676, percreta 661). A trophoblast count of ≥100 cells/high-power field was seen in 75.8% of cretas and 11.1% of controls ( P =0.0009). For the first time, we document the finding of chorionic villi intrusion into myometrial vascular spaces, which is highly specific of placenta creta. In addition, assessment of the amount of intermediate trophoblast using GATA3 immunohistochemistry can assist in the diagnosis. We hypothesize that placental invasion in placenta creta is due, at least partially, to transformation of low-resistance myometrial vessels leading to subsequent protrusion of villi into their lumens, in the context of absent decidua.